Case series analysis: Atrial fibrillation ablation with normal vs. left atrium enlargement - Baskoro, Shalahuddin Suryo; Saerang, Gebryel Dennis; Saputri, Vemmy Lian; Rizal, Ardian; Wikananda, Adhika Prastya; Waranugraha, Yoga (Universitas Brawijaya, 2025)
Background: Atrial fibrillation (AF) is one of the most common cardiac arrhythmias, and its incidence is gradually increasing worldwide. It can develop such life-threatening conditions as heart failure, myocardial infarction, and thromboembolism. Catheter ablation, as a minimally invasive procedure to eliminate AF triggers, demonstrates different levels of success, particularly in relation to the size of the left atrium (LA). Even though left atrium enlargement (LAE) associates with worse ablation outcomes, its mechanisms are poorly understood. Case Illustration: This case report investigated the treatment results in AF ablation cases with normal LA size and LAE. This case report described two paroxysmal AF patients who underwent catheter ablation. The patient of the first case is a 45-year-old male with normal LA Size, while the second case is a 55-year-old male with LAE. Both of these patients underwent pulmonary vein isolation (PVI) using a 3D mapping system. Sinus rhythm was gained in both patients before the discharge and both performed the ablation successfully. Conclusion: Left Atrial Enlargement (LAE) exposed patient to more difficult procedures and greater risk of recurrence. LA size is one of the predictor of long term outcome in AF ablation patients, but with proper management, the prognosis might still be favourable. More studies need to determine how to manage AF ablation in patients with high-risk characteristics